2022
DOI: 10.1007/s13127-022-00588-2
|View full text |Cite
|
Sign up to set email alerts
|

Historical biogeography highlights the role of Miocene landscape changes on the diversification of a clade of Amazonian tree frogs

Abstract: The diversification processes underlying why Amazonia hosts the most species-rich vertebrate fauna on earth remain poorly understood. We studied the spatio-temporal diversification of a tree frog clade distributed throughout Amazonia (Anura: Hylidae: Osteocephalus, Tepuihyla, and Dryaderces) and tested the hypothesis that Miocene mega wetlands located in western and central Amazonia impacted connectivity among major biogeographic areas during extensive periods. We assessed the group’s diversity through DNA-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…A non-coding region with a length of about 35 bp was found between trnS1 and ND5 in the five Hylidae sequences evaluated in this study. This non-coding region has been found in many species of Hylidae [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ], but did not exist in D. versicolor [ 54 ]. Whether this is the feature of all members of Hylidae will require more sequences to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…A non-coding region with a length of about 35 bp was found between trnS1 and ND5 in the five Hylidae sequences evaluated in this study. This non-coding region has been found in many species of Hylidae [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ], but did not exist in D. versicolor [ 54 ]. Whether this is the feature of all members of Hylidae will require more sequences to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these results seem to reinforce the idea that phyllomedusine frogs were able to survive in the lacustrine environment resulting from changes in the Amazonian drainage pattern when compared to other frog groups. Previous studies have already suggested the isolation and geographic expansion in other arboreal frogs may have been affected by the Miocene marine introgressions, depending on their capacity to exploit wetland environments for reproduction (e.g., Ortiz et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Our comparison with close relatives supports the separation of P. clarae from its most similar species like the sympatric P. albertus and P. aniptopalmatus. The 16S fragment as well as the gene COI are commonly used in amphibian DNA barcoding [34] and to explore cryptic diversity [35].…”
Section: Discussionmentioning
confidence: 99%